Application of water hyacinth flour (Eichhornia crassipes) in artificial feed on the feed quality and feed conversion ratio for bileh fish (Rasbora sp.) - Islama, Dini; Diansyah, Sufal; Diana, Farah; Saputra, Fazril; Rahmayanti, Fitria; Juliawati, Juliawati (Universitas Malikussaleh, 2023)
This study aims to determine the effect of water hyacinth (Eichhornia crassipes) powder application on artificial feed on feed quality and feed conversion ratio for bileh fish (Rasbora sp.) fry. This research was carried out from September to October 2022 at UPR Mina Mandiri Gampong Lhok Seumot, Beutong District, Nagan Raya Regency. This study used bile fish seeds measuring 2 - 2.25 cm in length as test fish. The experimental design used was a non-factorial, Completely Randomized Design (CRD) with four treatments and three replications. The level of treatment applied in the feed formulation was control feed without fermented water hyacinth flour substitution (P0), 5% fermented hyacinth flour substitution in feed (P1), 10% fermented water hyacinth flour substitution in feed (P2), water hyacinth flour substitution fermented 15% in feed (P3). Feed is given at satiation three times a day. The test parameters observed were the quality of the feed produced and the feed conversion ratio of the seeds of bileh fish (Rasbora sp.). The results showed that applying water hyacinth flour (Eichhornia crassipes) on artificial feed gave the same response to the quality of the feed produced but had a significant effect on the feed conversion ratio for bileh fish. The lowest (best) feed conversion ratio was obtained in the P3 treatment.Keywords: feed quality; feed conversion ratio; hyacinth flour; Rasbora sp.